Keratoconus with Central Serous Chorioretinopathy: A Rare Combination - Anastasia Tsiogka; Apostolos Gkartzonikas; Konstantinos Markopoulos; Iordanis Georgiou; George L. Spaeth (Case Reports in Ophthalmological Medicine)
Keratoconus and central serous chorioretinopathy are two rare diseases. They can occur together in some individuals. We report a case of a 48-year-old man, who presented to our clinic with decreased visual acuity on his left eye. Physical examination, biomicroscopy, corneal topography, and optical coherence tomography revealed keratoconus and central serous chorioretinopathy. We discuss the possible connection between these two conditions.